Role of oxidative stress mediated by glutathione-s-transferase in thiopurines' toxic effects. - Pelin, Marco; De Iudicibus, Sara; Fusco, Laura; Taboga, Eleonora; Pellizzari, Giulia; Lagatolla, Cristina; Martelossi, Stefano; Ventura, Alessandro; Decorti, Giuliana; Stocco, Gabriele (Chem Res Toxicol, 2015)
Azathioprine (AZA), 6-mercaptopurine (6-MP), and 6-thioguanine (6-TG) are antimetabolite drugs, widely used as immunosuppressants and anticancer agents. Despite their proven efficacy, a high incidence of toxic effects in patients during standard-dose therapy is recorded. The aim of this study is to explain, from a mechanistic point of view, the clinical evidence showing a significant role of glutathione-S-transferase (GST)-M1 genotype on AZA toxicity in inflammatory bowel disease patients. To this aim, the human nontumor IHH and HCEC cell lines were chosen as predictive models of the hepatic and intestinal tissues, respectively. AZA, but not 6-MP and 6-TG, induced a concentration-dependent superoxide anion production that seemed dependent on GSH depletion. N-Acetylcysteine reduced the AZA antiproliferative effect in both cell lines, and GST-M1 overexpression increased both superoxide anion production and cytotoxicity, especially in transfected HCEC cells. In this study, an in vitro model to study thiopurines' metabolism has been set up and helped us to demonstrate, for the first time, a clear role of GST-M1 in modulating AZA cytotoxicity, with a close dependency on superoxide anion production. These results provide the molecular basis to shed light on the clinical evidence suggesting a role of GST-M1 genotype in influencing the toxic effects of AZA treatment.